Manufacturing process of aluminum-titanium meltallizing composite coating applied to semiconductor equipment cavity

By using white corundum sand blasting, supersonic flame dissolving aluminum-titanium wire on the cavity of the semiconductor equipment, and vacuum heat treatment gradient treatment, the unevenness of the composite coating in roughness, binding force and porosity is solved, and a coating with high binding force, low porosity and excellent durability is achieved, which improves the service life and operating efficiency of the equipment.

CN119800271AActive Publication Date: 2025-04-11JIANGSU KAIWEITESI SEMICON TECH CO LTD

Patent Information

Application Number
CN202411861280.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-04-11
Estimated Expiration
2044-12-17

AI Technical Summary

Technical Problem

The aluminum-titanium melt-emitting composite coating of the existing semiconductor equipment cavity has unevenness in roughness, bonding force and porosity, resulting in insufficient adhesion, multiple particles, and poor corrosion resistance, which affects the service life and operating efficiency of the equipment.

Method used

White corundum sand blasting, supersonic flame dissipation aluminum-titanium wire is used, and the supersonic flame dissipation conditions and vacuum heat treatment parameters are optimized to improve the binding force and density of the composite coating.

Benefits of technology

The composite coating is achieved with high binding force, low porosity and excellent durability, and the performance and reliability of the coating in normal temperature and high temperature environments are improved, and the requirements of semiconductor process processes below 28nm are met.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005193266570000071
    Figure BDA0005193266570000071
  • Figure BDA0005193266570000091
    Figure BDA0005193266570000091
  • Figure BDA0005193266570000101
    Figure BDA0005193266570000101
Patent Text Reader

Abstract

The invention belongs to the technical field of thermal spraying, and particularly relates to a manufacturing process of an aluminum-titanium meltallizing composite coating applied to a semiconductor equipment cavity, which comprises the following steps: (1) carrying out sand blasting on the semiconductor equipment cavity by using a white corundum sand material; (2) residual sand materials are removed, cleaning and drying treatment are carried out, and a pretreated semiconductor equipment cavity is obtained; (3) aluminum wires are subjected to melt injection on the surface of the pretreated semiconductor equipment cavity through supersonic flame, and an aluminum melt injection coating is obtained; and (4) dissolving and injecting a titanium wire on the surface of the aluminum meltallizing coating by using hypersonic flame to obtain a titanium meltallizing coating, cleaning, drying and carrying out vacuum heat treatment. According to the prepared composite coating, the roughness meets the requirement, the meltallizing binding force is high, the coating is not prone to falling off, the porosity is low, and the coating is more compact.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of thermal spraying, and in particular relates to a process for manufacturing an aluminum-titanium thermal spraying composite coating applied to a semiconductor device cavity. Background Art

[0002] In semiconductor manufacturing, physical vapor deposition (PVD) is a key process for forming thin films such as metals and nitrides on silicon wafers or glass substrates. However, in this process, not only the target substrate will deposit the desired thin film, but the internal components of the PVD chamber will inevitably adsorb these materials. In order to enhance the adhesion of these semiconductor equipment cavities to the deposited film layer, prevent the film layer from peeling, and reduce the generation of particles in the cavity, thereby extending the service life of the semiconductor equipment cavity and improving the operating efficiency of the equipment, the commonly used methods currently include sandblasting and arc spraying to increase the roughness of the semiconductor equipment cavity surface.

[0003] ARC spraying is a surface thermal spraying technology. After a series of pre-treatments such as sandblasting and cleaning, the surface of the substrate is sprayed with molten spray coating droplets through airflow. The mechanical bonding force of the coating cooling and spreading is used to cover the surface of the substrate with a relatively uniform and rough coating.

[0004] The spray coating applied to the semiconductor equipment cavity still faces some challenges, especially in the three key performance indicators of roughness, bonding and porosity: 1. Roughness. During the spraying process, due to changes in factors such as spray angle, speed, and temperature, the surface roughness of the coating may be uneven, and local over-high or over-low conditions may occur. It is difficult to accurately control the size and distribution of the sprayed particles, which makes the microstructure of the coating surface less than ideal, affecting its smoothness and flatness. Rough surfaces are prone to accumulate residues during processing and increase the generation of particles, which is extremely unfavorable to the semiconductor manufacturing environment and may lead to an increase in product defect rates. A surface that is too rough may result in insufficient adhesion of the deposited film layer and increase the risk of film peeling. 2. Bonding. During the spraying process, if the substrate surface is improperly treated or the spraying parameters are inappropriate, interface defects such as voids and cracks may be formed between the coating and the substrate, which will weaken the bonding. Due to the different thermal expansion coefficients of the substrate material and the coating material, thermal stress will be generated during the heating and cooling process, which may cause the coating to crack or peel off. Insufficient bonding force will cause the coating to gradually peel off during use, shortening its service life, requiring frequent maintenance and replacement, and increasing production costs. Coating shedding will affect the corrosion resistance and wear resistance of the cavity, thereby reducing the overall performance and reliability of the equipment. 3. Porosity. During the spraying process, if the sprayed particles are not fully fused, or air is introduced during the spraying process, it may cause more pores to form inside the coating. Uneven pore distribution: The size and distribution of pores are uneven, and they may be concentrated in certain areas to form weak points, affecting the overall performance of the coating. The pores provide a penetration path for corrosive media, reducing the corrosion resistance of the coating, especially when it comes into contact with chemicals during the semiconductor manufacturing process, which makes corrosion more likely to occur. High porosity weakens the mechanical strength of the coating, making it more susceptible to damage under high temperature, high pressure or mechanical stress.

[0005] Existing technologies mainly rely on more sophisticated surface cleaning and pretreatment techniques, such as laser cleaning and chemical etching, to ensure that the substrate surface is clean and has appropriate roughness to enhance the adhesion of the coating. However, the porosity of the coating still cannot meet customer needs. And

[0006] Therefore, there is an urgent need for a process for manufacturing aluminum-titanium spray-sprayed composite coatings for semiconductor equipment cavities. Summary of the invention

[0007] The purpose of the present invention is to provide a process for manufacturing an aluminum-titanium composite coating for a semiconductor device cavity.

[0008] In order to achieve the above object, the present invention provides the following technical solutions:

[0009] A process for manufacturing aluminum-titanium spraying composite coating for semiconductor equipment cavity, comprising the following steps:

[0010] (1) Use white corundum abrasive to sandblast the semiconductor equipment cavity;

[0011] (2) first use high pressure water washing to remove residual sand material, then perform ultrasonic cleaning, and finally use nitrogen to blow dry and dry in an oven to obtain a pre-treated semiconductor device cavity;

[0012] (3) using a supersonic flame to spray aluminum wire on the surface of the pre-treated semiconductor device cavity to obtain an aluminum spray coating; the supersonic flame spraying conditions in step (3) are: current: 180-200A, voltage 25-30V, spraying distance 150-180mm, compressed air pressure 40-50psi.

[0013] (4) Using a supersonic flame to spray titanium wire on the surface of the aluminum spray coating, the supersonic flame spraying conditions in step (4) are: current: 180-200A, voltage 25-30V, spraying distance 150-180mm, compressed air pressure 40-50psi; the titanium spray coating is obtained, and after cleaning, drying and vacuum heat treatment, an aluminum-titanium spray composite coating for use in a semiconductor device cavity is obtained.

[0014] The existing aluminum spraying processes used in the electronics industry mainly include ARC (arc) spraying and flame (flame) spraying. ARC spraying easily produces spraying ash, resulting in the problem of high particles. In the prior art, ARC (arc) spraying and flame (flame) spraying are usually combined to improve the problem of high particles, but the corresponding cost increases. The present invention optimizes the entire process by design, only uses ARC (arc) spraying, and optimizes the supersonic flame spraying conditions to improve the problem of high particles. At the same time, the spraying conditions of the present invention can improve the bonding strength of the composite coating.

[0015] Furthermore, in the step (1), white corundum sand material with a mesh size of 20-30# is used to sandblast the semiconductor device cavity.

[0016] Furthermore, in the step (1), the sandblasting pressure is 0.3-0.5 Mpa, and the sandblasting distance is 160-180 mm.

[0017] Furthermore, in the step (2), the high-pressure water washing uses deionized water with a resistivity of 6-8 MΩ*cm and a water pressure of 70-80 bar.

[0018] Furthermore, in step (2), the ultrasonic cleaning uses deionized water with a resistivity of 6-8 MΩ*cm and an ultrasonic intensity of 8-10 W / inch. 2 .

[0019] Furthermore, in step (2), the drying time is 2-3 hours and the drying temperature is 145-155°C.

[0020] Furthermore, the supersonic flame spraying conditions in step (3) are: current: 180A, voltage 25V, spraying distance 150mm, compressed air pressure 40psi.

[0021] Furthermore, the supersonic flame spraying conditions in step (4) are: current: 180A, voltage 25V, spraying distance 150mm, compressed air pressure 40psi.

[0022] Furthermore, the vacuum heat treatment conditions in step (4) are: vacuum degree 4-6 mtorr, first at 260-270°C, keep warm for 1-2 hours; then keep warm at 230-240°C for 3-4 hours, and finally at 200-210°C, keep warm for 1-2 hours, and then cool with the furnace.

[0023] The present invention performs vacuum heat treatment on the composite coating by a gradient treatment method of vacuum heat treatment, which can improve the porosity of the composite coating. Under the vacuum heat treatment conditions of the present invention, the diffusion of metal atoms can gradually enable atoms in the coating material to migrate and fill tiny pores, and at the same time can help release the residual stress inside the composite coating and reduce the crack and pore expansion caused by stress concentration.

[0024] Furthermore, the purity of the titanium wire is ≥99.999%, and is purchased from Beijing Juguang Yingchuang Technology Co., Ltd.

[0025] Furthermore, the thickness of the aluminum spray coating in step (3) is 50±20 μm, and the thickness of the titanium spray coating in step (4) is 100±30 μm.

[0026] Furthermore, the ratio of the thickness of the aluminum spray coating to the thickness of the titanium spray coating is 1:(1.6-2.4).

[0027] During the test, it was found that the thickness of the aluminum spray coating and the titanium spray coating can affect the thickness of the aluminum spray coating of 50 ± 20 μm and the thickness of the titanium spray coating of 100 ± 30 μm, which can improve the bonding strength of the composite coating. Because the thickness of the aluminum spray coating and the titanium spray coating is closely related to the spraying conditions and vacuum heat treatment of the present invention, the synergistic effect of the three can improve the bonding strength of the composite coating. The aluminum layer, as the bottom layer, provides a preliminary protection and adhesion basis. The appropriate thickness can ensure that the aluminum layer evenly covers the surface of the substrate and can withstand the impact and heat of the subsequent titanium layer spraying. The bonding strength between the titanium layer and the aluminum layer directly affects the stability of the entire composite coating. A titanium layer of appropriate thickness can provide sufficient protection and bonding strength without adding too much stress. There is a synergistic effect between the thickness of the aluminum layer and the titanium layer, the spraying conditions and the vacuum heat treatment; reasonable thickness selection can ensure a good match between the layers, and the optimized spraying conditions ensure the quality of the coating; vacuum heat treatment further enhances the overall bonding strength and stability of the coating through stress release, diffusion and chemical reaction. And through the optimization of the above process steps, a composite coating with high bonding strength, low porosity and excellent durability can be obtained; this not only improves the performance of the coating at room temperature, but also ensures its long-term reliability in harsh working environments such as high temperature and high pressure.

[0028] And it was found during the test that when the ratio of the thickness of the aluminum spray coating to the thickness of the titanium spray coating is within the range of 1:(1.6-2.4), the bonding strength of the composite coating under variable temperature can be improved. The thermal expansion coefficients of the substrate, aluminum layer and titanium layer are usually different. When the temperature changes, the expansion degree of each layer of material is different, which may lead to stress concentration, especially at the interface, which may cause the coating to peel off or crack. When the thickness of the aluminum spray coating and the thickness of the titanium spray coating are within a specific ratio range, when the ratio of the thickness of the aluminum spray coating to the thickness of the titanium spray coating is 1:(1.6-2.4), the bonding strength of the composite coating under variable temperature can be effectively improved. This ratio helps to balance the stress between the layers and optimize the microstructure, and under this condition, vacuum heat treatment can better release stress, promote diffusion and form stable intermetallic compounds, further enhancing the bonding strength and overall performance of the coating.

[0029] Compared with the prior art, the advantages and beneficial effects of the present invention are:

[0030] 1. The present invention provides a process for producing an aluminum-titanium spray-sprayed composite coating for a semiconductor device cavity. The prepared composite coating has a roughness that meets the requirements, a high spray-sprayed bonding strength, is not easy to fall off, has a low porosity, and is denser.

[0031] 2. The present invention uses only ARC (arc) spraying, and by optimizing the supersonic flame spraying conditions, the problem of high particles can be improved. Under normal circumstances, the measurement result is less than 1, which can meet the semiconductor process requirements below 28nm. At the same time, the spraying conditions of the present invention can improve the bonding strength of the composite coating.

[0032] 3. The present invention performs vacuum heat treatment on the composite coating by means of gradient treatment, thereby improving the porosity of the composite coating.

[0033] 4. The thickness of the aluminum spray coating and the titanium spray coating in the present invention can be affected. The thickness of the aluminum spray coating is 50±20 μm, and the thickness of the titanium spray coating is 100±30 μm, which can improve the bonding force of the composite coating.

[0034] 5. In the present invention, when the ratio of the thickness of the aluminum spray coating to the thickness of the titanium spray coating is within the range of 1:(1.6-2.4), the bonding strength of the composite coating under variable temperature can be improved. DETAILED DESCRIPTION

[0035] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] Example 1

[0037] This embodiment provides a process for manufacturing an aluminum-titanium composite coating for a semiconductor device cavity, comprising the following steps:

[0038] (1) Use 24# white corundum abrasive to sandblast the PVD equipment cavity (physical deposition cavity); the sandblasting pressure is 0.4Mpa, and the sandblasting distance is 170mm;

[0039] (2) First, use high-pressure water washing to remove the residual sand material. The high-pressure water washing uses deionized water with a resistivity of 8MΩ*cm and a water pressure of 75bar; then perform ultrasonic cleaning. The ultrasonic cleaning uses deionized water with a resistivity of 8MΩ*cm and an ultrasonic intensity of 9W / inch 2 ; Finally, dry with nitrogen and dry in an oven for 3 hours at a drying temperature of 150°C to obtain a pre-treated semiconductor device cavity;

[0040] (3) using supersonic flame to spray aluminum wire on the surface of the pre-processed semiconductor device cavity, the supersonic flame spraying conditions are: current: 180A, voltage 25V, spraying distance 150mm, compressed air pressure 40psi; to obtain an aluminum spray coating; the aluminum spray coating is 50μm; the aluminum wire grade is 1070A;

[0041] (4) Using supersonic flame to spray titanium wire on the surface of aluminum spray coating, the purity of the titanium wire is ≥99.999%. Purchased from Beijing Juguang Yingchuang Technology Co., Ltd.; supersonic flame spraying conditions are: current: 180A, voltage 25V, spraying distance 150mm, compressed air pressure 40psi; titanium spray coating is obtained, and the thickness of the titanium spray coating is 100μm; after cleaning, drying and vacuum heat treatment, the vacuum heat treatment conditions are: vacuum degree 5mtorr, first at 265℃, keep warm for 1.5h; then keep warm at 235℃ for 3.5h, and finally at 205℃, keep warm for 1.5h, and then cool with the furnace; aluminum-titanium spray composite coating for semiconductor equipment cavity is obtained.

[0042] Table 1 Supersonic flame spraying conditions for steps (3) and (4)

[0043]

[0044] The difference between Examples 2-6 and Comparative Examples 1-3 and Example 1 is that the supersonic flame spraying conditions are different, as shown in Table 1.

[0045] Comparative Example 4

[0046] The difference between this comparative example and Example 1 is that the supersonic flame spraying conditions are: current: 170A, voltage 20V, spraying distance 180mm, compressed air pressure 35psi.

[0047] Comparative Example 5

[0048] The difference between this comparative example and Example 1 is that the supersonic flame spraying conditions are: current: 210A, voltage 35V, spraying distance 180mm, compressed air pressure 55psi.

[0049] Comparative Example 6

[0050] The difference between this comparative example and Example 1 is that the vacuum heat treatment conditions are: the vacuum heat treatment conditions are: vacuum degree 5mtorr, first at 280°C, keep warm for 3h; then keep warm at 250°C for 1h, and finally the temperature is 180°C, keep warm for 3h, and then cool with the furnace.

[0051] Comparative Example 7

[0052] The difference between this comparative example and Example 1 is that the vacuum heat treatment conditions are: vacuum degree 5 mtorr, temperature 260° C., insulation time 7 h, and then cooling with the furnace.

[0053] Comparative Example 8

[0054] The difference between this comparative example and Example 1 is that the thickness of the aluminum spray coating in step (3) is 100 μm, and the thickness of the titanium spray coating in step (4) is 50 μm.

[0055] Comparative Example 9

[0056] The difference between this comparative example and Example 1 is that the thickness of the aluminum spray coating in step (3) is 75 μm, and the thickness of the titanium spray coating in step (4) is 75 μm.

[0057] Performance Testing

[0058] The composite coatings of Examples 1-6 and Comparative Examples 1-9 were subjected to performance tests.

[0059] 1. Referring to GB / T8642-2002, the bonding strength between the composite coating and the cavity was measured at 25°C and variable temperature conditions; the variable temperature conditions were: the composite coating was placed at 25°C, 70°C, and 100°C for 24 hours each, and then the bonding strength was measured at 25°C.

[0060] 2. Refer to GB / T131-2009 to measure the roughness;

[0061] 3. Use LEICADMI5000M electron microscope to measure the porosity.

[0062] 4. Simulate the actual use environment of the composite coating, observe the time for which the coating does not crack or peel off, calculate the service life, and evaluate the impact of long-term thermal stress on the bonding strength.

[0063] The results are shown in Table 1.

[0064] Table 1 Performance test results

[0065]

[0066]

[0067] From the above performance test results, it can be seen that the comprehensive performance of the composite coatings of Examples 1-6 is excellent, especially the comprehensive performance of Example 1 is the most outstanding, with a bonding force of up to 36MPa and a porosity of 2.2%. At the same time, the particle detection ea≥0.3μm of Example 1 is 0.31 / cm 2Under normal circumstances, a measurement result less than 1 can meet the semiconductor process requirements below 28nm. The detection ea≥0.3μm of Examples 2-6 is also within 0.50~1 / cm 2 within the range.

[0068] However, the comparative examples are significantly worse than the embodiments in terms of corresponding performance tests because they do not adopt the necessary technical solutions. In comparative examples 1-3, the melting distance is changed, the bonding force and porosity are reduced, and the temperature resistance is deteriorated. In comparative examples 4-5, the current, voltage and compressed air pressure are changed, the bonding force and porosity are reduced, and the temperature resistance is deteriorated, which proves that only under the supersonic flame melting conditions of the present invention, the composite coating will have a higher effect. The vacuum heat treatment conditions in comparative examples 6-7 are different. From the results, it can be seen that the porosity effect of the coating is deteriorated. It can be seen from comparative examples 8-9 that the thickness of the aluminum layer and the titanium layer is changed, the bonding force under the variable temperature is reduced, and the service life of the composite coating is also reduced. The above experimental results further prove the importance of the technical solution defined in the present invention for its technical effect.

[0069] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A process for producing aluminum-titanium composite coating for semiconductor equipment cavity, characterized in that: The following steps are involved: (1) Use white corundum abrasive to sandblast the semiconductor equipment cavity; (2) first use high pressure water washing to remove residual sand material, then perform ultrasonic cleaning, and finally use nitrogen to blow dry and dry in an oven to obtain a pre-treated semiconductor device cavity; (3) using a supersonic flame to spray aluminum wire on the surface of a pre-treated semiconductor device cavity to obtain an aluminum spray coating; (4) A supersonic flame is used to melt-spray titanium wire on the surface of the aluminum spray coating to obtain a titanium spray coating, which is then cleaned, dried and vacuum heat treated. The vacuum heat treatment conditions are: vacuum degree 4-6 mtorr, first at 260-270°C, keep warm for 1-2 hours; then keep warm at 230-240°C for 3-4 hours, and finally at 200-210°C, keep warm for 1-2 hours, and then cool with the furnace; an aluminum-titanium spray composite coating for use in the cavity of semiconductor equipment is obtained.

2. The process for manufacturing aluminum-titanium composite coating for semiconductor equipment cavity according to claim 1 is characterized in that: In the step (1), white corundum sand material with a mesh size of 20-30# is used to sandblast the semiconductor equipment cavity.

3. The process for manufacturing aluminum-titanium composite coating for semiconductor equipment cavity according to claim 1 is characterized in that: In the step (1), the sandblasting pressure is 0.3-0.5 MPa, and the sandblasting distance is 160-180 mm.

4. The process for manufacturing aluminum-titanium composite coating for semiconductor equipment cavity according to claim 1 is characterized in that: In the step (2), the high pressure water washing uses deionized water with a resistivity of 6-8 MΩ*cm and a water pressure of 70-80 bar.

5. The process for manufacturing aluminum-titanium composite coating for semiconductor equipment cavity according to claim 1 is characterized in that: In step (2), ultrasonic cleaning uses deionized water with a resistivity of 6-8 MΩ*cm and an ultrasonic intensity of 8-10 W / inch 2 .

6. The process for manufacturing aluminum-titanium composite coating for semiconductor equipment cavity according to claim 1 is characterized in that: In the step (2), the drying time is 2-3 hours and the drying temperature is 145-155°C.

7. The process for manufacturing aluminum-titanium composite coating for semiconductor equipment cavity according to claim 1 is characterized in that: The supersonic flame spraying conditions in step (3) are: current of 180-200A, voltage of 25-30V, spraying distance of 150-180mm, and compressed air pressure of 40-50psi.

8. The process for manufacturing aluminum-titanium composite coating for semiconductor equipment cavity according to claim 1 is characterized in that: The supersonic flame spraying conditions in step (4) are: current of 180-200A, voltage of 25-30V, spraying distance of 150-180mm, and compressed air pressure of 40-50psi.

9. The process for manufacturing aluminum-titanium composite coating for semiconductor equipment cavity according to claim 1 is characterized in that: The thickness of the aluminum spray coating in step (3) is 50±20 μm, and the thickness of the titanium spray coating in step (4) is 100±30 μm.

10. The process for manufacturing aluminum-titanium composite coating for semiconductor equipment cavity according to claim 9, characterized in that: The ratio of the thickness of the aluminum spray coating to the thickness of the titanium spray coating is 1:(1.6-2.4).

Citation Information

Patent Citations

  • Preparation technology of aluminum meltallizing layers applied to electronic industry cavity equipment

    CN108070815A

  • Dissolving technology for improving service life of aluminum-dissolving layer of semiconductor cavity

    CN109182945A

  • Method for sputtering of protective coatings for an intermetallic alloy based on titanium gamma-aluminide

    RU2716570C1

  • Diffusion heat treated thermally sprayed coatings

    US6165286A

Cited By

  • Preparation method of titanium-aluminum composite meltallizing layer for cavity of generic semiconductor equipment

    CN122235624A